Integrating receptor signal inputs that influence small Rho GTPase activation dynamics at the immunological synapse. - Makrogianneli, K; Carlin, L; Keppler, MD; Matthews, DR; Ofo, E; Coolen, A; Ameer-Beg, S; Barber, P; Vojnovic, B; Ng, T (2009)
The Rho GTPase Cdc42 regulates cytoskeletal changes at the immunological synapse (IS) that are critical to T-cell activation. By imaging fluorescent activity biosensors (Raichu) using fluorescence lifetime imaging microscopy, Cdc42 activation was shown to display kinetics that are conditional on the specific receptor input (through two IS-associated receptors, CD3 and beta1 integrin). CD3-triggered Cdc42 activity is dependent on the cyto-2 (NPIY) motif of the beta1 integrin cytoplasmic domain. Perturbations of the ezrin-radixin-moesin (ERM) function blocked CD3- and beta1-dependent increases in Cdc42 activity. Both IS-associated receptors probably lie on a serial molecular pathway and transduce signals through the ERM-dependent machinery that is responsible for the remodeling and stabilization of the synapse. Cdc42 activity is impaired in beta1 integrin-deficient T cells that form conjugates with antigen-presenting cells but is partially restored in the context of an antigen-specific synapse. This restoration of Cdc42 activity is due, at least in part, to the recruitment and activation of beta2 integrin.